Coping Potential of Humor in Traumatic Experiences (Review) - Sofiya L. Nemkova; Elena M. Ivanova (Вестник Московского университета. Серия 14: Психология)
Background. The social and political world situation of recent years has reawakened mass interest in the topic of psychotrauma. Studying this phenomenon, researchers raise questions about the ways to cope with the consequences of a traumatic experience. Humor is recognized as one of the important coping strategies in this case. However, this issue evokes a discussion on the appropriateness and effectiveness of using different variations of humor in traumatic situations. Objective. The study aimed to examine possible positive and negative effects of humor when processing a traumatic experience. Methods. The study is a literature review. Results. Research data suggest that humor can both be an effective mechanism of psychological defense in crisis, traumatic and extreme situations, and may as well prevent successful interpersonal interaction, reducing the necessary level of social support. In particular, the use of dark humor, as well as aggressive and self-defeating humor styles, in psychotrauma is controversial. Numerous studies confirm the special role of dark humor for professionals at “high-risk” jobs. Conclusions. Humor is indeed an important coping mechanism but the variety of its functions, types and styles, as well as different contexts of its use, do not allow us to oversimplify and unambiguously consider its effects. There are both positive and negative effects of humor when processing traumatic experiences. The question of the coping potential of dark humor, as well as aggressive and self-defeating humor styles, remains open and promising for study. It is known that they play an important role for coping in extreme situations in “high-risk” professions, but they can also be an indicator of burnout in case of fixation.